Analysis of the Effectiveness of Radar and Drone Technology in Countering Maritime Security Threats: A Literature Review - Sugiharto, Barry (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study aims to analyze the effectiveness of the use of radar and drone technology in counteracting maritime security threats in Indonesia. The main focus is directed at the extent to which the two technologies can complement each other, the implementation obstacles faced, and strategic solutions to improve marine surveillance. Methodology/approach: This study uses secondary data collected from various sources of literature, institutional regulations, and the results of previous studies relevant to law enforcement in Indonesian waters. The data is analyzed qualitatively and presented descriptively. Results/findings: The main challenges of Indonesia's maritime security include the area of the sea that is difficult to reach, weak surveillance, and the development of various forms of threats such as smuggling and border violations. Radars and drones have great potential in detecting and monitoring illegal activities at sea. However, challenges such as limited reach, technical capabilities, human resources, and suboptimal integration between institutions are still the main obstacles. Therefore, it is necessary to modernize equipment, train personnel, and improve coordination between maritime institutions. Conclusions: The study concludes that integrating radar and drone technologies significantly enhances Indonesia’s maritime security. Radar ensures wide detection coverage, while drones provide real-time monitoring and flexibility. Yet, limited infrastructure and coordination reduce effectiveness. Strengthening technology, training, and interagency collaboration is essential to improve maritime defense efficiency and responsiveness. Limitations: Lies in an approach that uses only secondary data, without the support of live interviews or field data. For this reason, follow-up studies are recommended to involve primary data from institutions such as the Indonesian Navy and Bakamla. Contribution: Future research is also expected to explore other supporting technologies, such as surveillance satellites and AI, as well as examine regulatory and policy factors in more depth.